Curbing Inflammation in hemorrhagic trauma: a review - GODINHO,MAURICIO (2015)
Trauma is one of the world's leading causes of death within the first 40 years of life and thus a significant health problem. Trauma accounts for nearly a third of the lost years of productive life before 65 years of age and is associated with infection, hemorrhagic shock, reperfusion syndrome, and inflammation. The control of hemorrhage, coagulopathy, optimal use of blood products, balancing hypo and hyperperfusion, and hemostatic resuscitation improve survival in cases of trauma with massive hemorrhage. This review discusses inflammation in the context of trauma-associated hemorrhagic shock. When one considers the known immunomodulatory effects of traumatic injury, allogeneic blood transfusion, and the overlap between patient populations, it is surprising that so few studies have assessed their combined effects on immune function. We also discuss the relative benefits of curbing inflammation rather than attempting to prevent it.